Legal Analysis of Economic Exploitation of Children in the Juvenile Criminal Justice System - Voni Cahya Br Siregar; Tahasak Sahay; Yurika F. Dewi; Putri Fransiska Purnama Pratiwi (Jurnal Locus Penelitian dan Pengabdian, 2026)
The phenomenon of economic exploitation of children in Indonesia shows that the legal protection system for children as subjects of rights is still weak. This study aims to analyze and analyze the formulation of regulations to ensnare child exploitation perpetrators in the Indonesian criminal justice system. The research method used is normative juridical with legislative, conceptual, and case approaches. Data sources include Law Number 35 of 2014 concerning Child Protection, Law Number 11 of 2012 concerning the Child Criminal Justice System, as well as various studies and reports of institutions such as KPAI and UNICEF. The results of the study show that although normative protection for children has been comprehensively regulated, its implementation has not been optimal due to weak coordination between law enforcement, low sentences, and lack of recovery mechanisms for victims. The application of the concepts of vicarious liability and strict liability is still limited, even though both can expand the scope of liability, including for corporations that profit from child exploitation. Legal reform is needed through increasing criminal sanctions, affirming mandatory restitution, and strengthening the child-friendly justice system with the active role of KPAI, LPSK, and the Children's Correctional Center. Thus, the effectiveness of law enforcement against child exploitation can only be achieved if normative instruments are accompanied by implementation mechanisms that are oriented towards the recovery and the best interests of children.